2018
DOI: 10.3390/su10124639
|View full text |Cite
|
Sign up to set email alerts
|

Is Southern Xinjiang Really Unsafe?

Abstract: Destination image and safety not only affect tourist decision-making but also the sustainable development of tourist destinations. Some tourist destinations are too vulnerable to defend against emergency tourist crises, and tourists’ perceived safety can be severely biased, which is then deepened by media panic caused by the publication of excessive negative reports. This paper discusses the mechanism of perceived safety and perceived image on tourist behavioral intention, as well as the inter-group difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 111 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…The results showed that there was no deviation and the data were normally distributed. Additionally, we used Harman's single factor test, the multitrait-multimethod model, the partial correlation method, and other methods to test the bias of the data [121]. The results showed that there was no common method bias in this study; thus, it was suitable for further analysis.…”
Section: Analysis Of Normality and Common Methods Biasmentioning
confidence: 89%
See 1 more Smart Citation
“…The results showed that there was no deviation and the data were normally distributed. Additionally, we used Harman's single factor test, the multitrait-multimethod model, the partial correlation method, and other methods to test the bias of the data [121]. The results showed that there was no common method bias in this study; thus, it was suitable for further analysis.…”
Section: Analysis Of Normality and Common Methods Biasmentioning
confidence: 89%
“…Finally, 665 valid questionnaires were obtained after eliminating the invalid questionnaires, with a recovery rate of 78.20% and an effective rate of 85.04%. The number of collected questionnaires was much greater than 10 times the number of indicators; thus, the minimum requirements for establishing an effective structural equation model were met [120][121][122]. Therefore, the number of samples obtained could well meet the needs of the study.…”
Section: Samplingmentioning
confidence: 99%
“…The normality of the data was analyzed via the kurtosis and skewness tests, which showed that the data were distributed normally. We tested several methods including the partial correlation method, the multi-trait-multimethod model, and Harman's single factor test to avoid the impact of common method bias [69,70]. The results indicated that there was no common method bias in the model.…”
Section: Analysis Of Normality and Common Methods Biasmentioning
confidence: 99%
“…The measurement dimensions of perceived value are not uniform due to the differences in the attributes and performances of tourist destinations, tourists' desires and expectations [33]. Prebensen (2017) developed a six-dimensional scale including quality value, economic value, novelty value, knowledge value, emotional value, and social value [34], which is widely used in tourism researches [3,11,35]. Quality value refers to tourists' perception of the quality of products or services [36,37]; economic value refers to tourists' perception of the value of the return [38]; novelty value is the value characteristics that tourists obtain from a product or service that are surprising and fresh [39]; knowledge value means that a tourist can learn from a product or the service, satisfying their thirst for knowledge [36]; emotional value is the emotional utility that tourists derive from a product or service, such as the pleasure and emotional satisfaction of a travel experience [36,40]; and social value is the equivalent utility of a traveler's social identity from a product or service and the enhancement of the traveler's self-image [41].…”
Section: Perceived Valuementioning
confidence: 99%